2013
DOI: 10.1073/pnas.1216375110
|View full text |Cite
|
Sign up to set email alerts
|

Mutant methionyl-tRNA synthetase from bacteria enables site-selective N-terminal labeling of proteins expressed in mammalian cells

Abstract: Newly synthesized cellular proteins can be tagged with a variety of metabolic labels that distinguish them from preexisting proteins and allow them to be identified and tracked. Many such labels are incorporated into proteins via the endogenous cellular machinery and can be used in numerous cell types and organisms. Though broad applicability has advantages, we aimed to develop a strategy to restrict protein labeling to specified mammalian cells that express a transgene. Here we report that heterologous expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 66 publications
(54 reference statements)
0
62
0
Order By: Relevance
“…Combining this methodology with cell type specific protein labeling 20,42 will offer a valuable tool to dissect proteome dynamics in different cell populations in complex organs such us the nervous system. Finally, by demonstrating the robustness of our method for in vivo applications, in this report and a recent study, 43 we show for the first time the direct detection of biotinylated labeled in intact animals after a short pulse of AHA labeling.…”
Section: Resultsmentioning
confidence: 99%
“…Combining this methodology with cell type specific protein labeling 20,42 will offer a valuable tool to dissect proteome dynamics in different cell populations in complex organs such us the nervous system. Finally, by demonstrating the robustness of our method for in vivo applications, in this report and a recent study, 43 we show for the first time the direct detection of biotinylated labeled in intact animals after a short pulse of AHA labeling.…”
Section: Resultsmentioning
confidence: 99%
“…showed that both E. coli and mammalian cells expressing a mutant MetRS are able to utilize ANL as a surrogate for methionine in protein synthesis, while wild-type cells are inert to ANL and proteins made in these cells are not labeled [42,43‱]. In co-culture experiments, labeling of newly synthesized proteins with affinity reagents or fluorescent dyes is restricted to cells expressing the mutant MetRS, therefore enabling cell-specific enrichment, identification and visualization, even in mixtures of different cell types.…”
Section: New Developmentsmentioning
confidence: 99%
“…58 Interestingly, Anl replaces methionine selectively at N-terminal positions not at internal sites. Site-selectivity occurs because NLL-EcMetRS catalyzes aminoacylation only of the mammalian initiator tRNA Met , not the mammalian elongator tRNA Met .…”
Section: Spatially Resolved Proteomic Analysismentioning
confidence: 99%